Communication and enviroment sustainability and risks - Hamidah Abd Hamid (Penerbit Universiti Sains Malaysia, 2012)
There ia a dearth of literature on environment communication within the non-western world. The few existing ones are scattered and not easily available. Thus, there ia a dire need to document research and literature in the field. The opportunity arose at the 2009 International Conference on Communication and Environment held in Penang, Malaysia. The international conference with the theme " Transformation for a Sustainable Tomorrow", organised by the School of Communication, USM, attracted scholars, practitioners, and activists from around the world to listen and deliberate on various aspects of communication and environment. The post-conference review resulted the selection of 24 papers to be compiled into this edited volume.